2021
DOI: 10.1093/alcalc/agab045
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Persistence of Nalmefene Treatment for Alcohol Dependence. Results from Two Post-authorisation Safety Studies

Abstract: Aims Two post-authorisation studies assessed the safety and persistence of patients’ use of nalmefene. Methods The START study (EUPAS5678) was a non-interventional, multi-country, prospective, 18-month (8 follow-up visits) cohort study including outpatients initiating nalmefene for the first time. The multi-database retrospective cohort study (MDRC, EUPAS14083) included baseline and follow-up data from German, Swedish and UK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We know of no study in the alcohol literature showing an e cacious medicine with an AE pro le similar to placebo. Naltrexone has a Food and Drug Administration black box warning for liver toxicity; post-authorization data for nalmefene has noted rare but serious CNS adverse events 43 non-compliance is reported with acamprosate due to gastrointestinal discomfort (with less than 30% of patients being able to tolerate its long-term administration) 44 , and there are potentially fatal AEs with disul ram if a patient concomitantly consumes alcohol. AD04 is a unique medicine that could gain favor among non-specialist clinical practitioners, especially as both 6-month pill-taking and study compliance exceeded 95% and 70%, respectively, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We know of no study in the alcohol literature showing an e cacious medicine with an AE pro le similar to placebo. Naltrexone has a Food and Drug Administration black box warning for liver toxicity; post-authorization data for nalmefene has noted rare but serious CNS adverse events 43 non-compliance is reported with acamprosate due to gastrointestinal discomfort (with less than 30% of patients being able to tolerate its long-term administration) 44 , and there are potentially fatal AEs with disul ram if a patient concomitantly consumes alcohol. AD04 is a unique medicine that could gain favor among non-specialist clinical practitioners, especially as both 6-month pill-taking and study compliance exceeded 95% and 70%, respectively, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A series of withdrawal symptoms occur when alcohol consumption is terminated or abruptly reduced and can only be alleviated by the repeated use of alcohol or pharmacologically similar substances. 64 Alcohol addiction has become a major risk factor for death and disability, affecting approximately 4% of the global adult population. 27 A WHO survey indicated that 3.8% of the 2 billion people worldwide who consume alcoholic beverages are diagnosed with alcohol addiction.…”
Section: Why Ald Should Be Taken Seriously?mentioning
confidence: 99%